Hubungan Antara Media Pembelajaran dan Minat Belajar Fisika: Studi Kasus pada Fluida Statis - Ramdani, Gifar; Nursabila, Nursabila (Universitas Garut, 2024)
This study aims to analyze the relationship between the use of learning media and students' interest in physics, particularly in static fluid topics. The research employed a qualitative method with a case study approach involving 11th-grade students at a private high school in Garut. Data were collected through questionnaires, observations, and document studies, then analyzed using Miles and Huberman's qualitative data analysis techniques. The findings indicate that the average student interest in learning physics is relatively low, at 39.3%. The highest-rated indicator is